The future of animal law - Favre, David S., 1946- (Edward Elgar Publishing, 2021)
"This unique book establishes potential future avenues within the law to enhance the welfare of animals and grant them recognised legal status. Charting the direction of the animal-human relationship for future generations, it explores the core concepts of property law to demonstrate how change is possible for domestic animals. As an ethical context for future developments the concept of a 'right of place' is proposed and developed. The Future of Animal Law focuses on dogs as companion animals who provide the political motivation for legislative change, contextualising the role of companion animals within the concept of family and the future implications of this position. It compares the US approach with materials from other common law jurisdictions, illustrating how a number of existing laws support the claim that companion animals are already on the path to personhood. David Favre recommends model language for new animal friendly laws in addition to suggesting amendments to existing legislation including the US federal Animal Welfare Act. Forward thinking and innovative, this indispensable book will engage all those with an interest in the issues around enhanced welfare and rights for animals, including students, scholars and lawyers involved in animal law, as well as leaders of non-profit organizations"--